Efficacy of Government-Sponsored Community Health Programs for Older Adults: A Systematic Review of Published Evaluation Studies - Arun Chandrashekhar; Harshad P. Thakur (Frontiers Media S.A., 2022)
Objective: Population aging is an ongoing challenge for global health policy and is expected to have an increasing impact on developing economies in years to come. A variety of community health programs have been developed to deliver health services to older adults, and evaluating these programs is crucial to improving service delivery and avoiding barriers to implementation. This systematic review examines published evaluation research relating to public and community health programs aimed at older adults throughout the world.Methods: A literature search using standardized criteria yielded 58 published articles evaluating 46 specific programs in 14 countries.Results: Service models involving sponsorship of comprehensive facilities providing centralized access to multiple types of health services were generally evaluated the most positively, with care coordination programs appearing to have generally more modest success, and educational programs having limited effectiveness. Lack of sufficient funding was a commonly-cited barrier to successful program implementations.Conclusion: It is important to include program evaluation as a component of future community and public health interventions aimed at aging populations to better understand how to improve these programs.